2007
DOI: 10.1016/j.cep.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Laminar flow in chevron-type plate heat exchangers: CFD analysis of tortuosity, shape factor and friction factor

Abstract: Laminar or low Reynolds number flows are usually obtained when liquid foods with high viscosity are processed in plate heat exchangers (PHEs). The tortuosity coefficient is a key parameter used by PHEs manufacturers to estimate Fanning friction factors and convective heat transfer coefficients. Using the finite-element computational fluid dynamics program POLYFLOW ® , fully developed laminar flows in double-sine chevrontype PHEs passages are analysed in this work. The corrugation angle and channel aspect ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 38 publications
(72 reference statements)
1
31
0
1
Order By: Relevance
“…(12)) for elaborate calculations. Fernandes et al (2007) found a good agreement between their numerical data (Eq. (10)) and the data from Wanniarachchi et al…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…(12)) for elaborate calculations. Fernandes et al (2007) found a good agreement between their numerical data (Eq. (10)) and the data from Wanniarachchi et al…”
Section: Introductionsupporting
confidence: 72%
“…1) developed by Fernandes et al (2007) differs from the unitary cell used by Ciofalo et al (1996) and Mehrabian and Poulter (2000) since it includes five contact points (four in the corners and one in the centre of the cell) instead of four (all in the corners). Fernandes et al (2007) established the referred unitary cell after observing the periodicity of the flow during the cooling of stirred yoghurt in half of a chevron-type PHE passage (Fernandes et al, 2005(Fernandes et al, , 2006Maia et al, 2007). In both approaches, the numerical results compared well with experimental data (Afonso et al, 2003;Wanniarachchi et al, 1995) from the literature; but the former approach (unitary cells) provides lower CPU times.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 3 more Smart Citations